Book Review: Elementary Change: Moving Toward Systemic School Reform in Rural Kentucky - Nancy Jennings (Journal of Research in Rural Education, 2001)
This book is a well-researched, well-written, and clearly organized qualitative study of six elementary schools' responses to Kentucky's decade-long school reform, KERA. Like much of the research that has been published on KERA (e.g., Whitford & Jones, 2000), this account offers readers both interesting information on the relationship between school practice and state reform, and a good story about an ambitious state policy. Although the authors do not break new theoretical ground with their findings, their exceptionally detailed analysis of schools undertaking comprehensive reform offers even the most informed reader a vivid road map of the difficulties schools face in implementing state reforms.